2007
DOI: 10.1097/mao.0b013e31815aee21
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic Versus Intravenous Delivery of Methylprednisolone to Cochlear Perilymph

Abstract: IT administration of methylprednisolone in humans results in much higher perilymph concentrations and much lower systemic concentrations than IV administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
161
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(181 citation statements)
references
References 25 publications
8
161
0
4
Order By: Relevance
“…Based on our new data, it now appears likely that elimination from perilymph occurs more rapidly than from the middle ear. The high rate of elimination seen here is more compatible with Plontke et al's (2008a) analysis of methylprednisolone data from humans (Bird et al 2007), which suggested an elimination half-time of 27 mins (also based on similar elimination rate from ST and the middle ear). Differences between all these studies could also arise from the fact that different glucocorticoids were used and each could exhibit different kinetics.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Based on our new data, it now appears likely that elimination from perilymph occurs more rapidly than from the middle ear. The high rate of elimination seen here is more compatible with Plontke et al's (2008a) analysis of methylprednisolone data from humans (Bird et al 2007), which suggested an elimination half-time of 27 mins (also based on similar elimination rate from ST and the middle ear). Differences between all these studies could also arise from the fact that different glucocorticoids were used and each could exhibit different kinetics.…”
Section: Discussionsupporting
confidence: 78%
“…There have been numerous pharmacokinetic studies of locally-applied corticosteroids in animals (Nomura 1984;Parnes et al 1999;Chandrasekhar et al 2000;Bachmann et al 2001;Hahn et al 2006Hahn et al , 2012Liu et al 2006;Plontke et al 2008b;Yang et al 2008;Wang et al 2009;Borden et al 2011;Salt et al 2011a) and humans (Bird et al 2007;Bird et al 2011), but only a subset of these studies has been analyzed quantitatively to derive an elimination rate. Plontke and analyzed prednisoline data of Bachmann et al (2001) from guinea pigs and found it to be consistent with an elimination half-time from perilymph of 130 min.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gd remains in the fluid space that it was applied to for 24 h or longer. In contrast, other drugs such as steroids readily enter endolymph (Parnes et al 1999) and are cleared rapidly from the cochlear fluids (Bird et al 2007;Plontke et al 2008). It remains uncertain whether the predominant entry of Gd in the region of the stapes is a general property of the inner ear, or whether this reflects a characteristic specific to Gd, perhaps related to a very low rate of Gd entry through the RW membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Intratympanic (IT) treatment options are good alternatives in patients that do not respond to medical treatment. It has been shown that medications administered into the middle ear pass into the inner ear through oval and round windows, in very high concentrations [2] . IT gentamicin application has been widely accepted in Meniere's disease because of the dominant vestibulotoxic effect of the agent [3,4] .…”
Section: Introductionmentioning
confidence: 99%